MOTIVASI KERJA KARYAWAN HOUSEKEEPING DI HOTEL ZAIRA PEKANBARU - ", Asman; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at Hotel Zaira Pekanbaru. This study aims to determine working motivation of housekeeping at Zaira Hotel. This study aims a). To analyze the factors that influence the working activity of Housekeeping at Zaira Pekanbaru Hotel. b). To know what efforts were made by the company in increasing working motivation of Housekeeping at Zaira Pekanbaru Hotel. The sample used in this study were 9 respondents (people). This research useddescriptive analysis method that is a technique to describes or depicts something, either in the form of drawings or photographs obtained from field data or researcher describes research results with pictures and can also mean to explain with words in thereport for complementarity Boundary problem in this study, the author discusses only working motivation of Housekeeping at Zaira Pekanbaru Hotel and any attempts by the company to improve working motivation of Housekeeping at Zaira Pekanbaru Hotel. Apart from these aspects of the author will not be discussed. The identification of this research to determine how is the working motivation of Housekeeping at Zaira Pekanbaru Hotel? and What attempts did implement by the company to improve it? Keywords: Phisical needs, Security needs, Social needs, Esteem needs, self actualization needs.